Technology -Based Business Idea Blueprint : JAL-JA Restaurant / Siti Nur Athirah Adibah Maiddin - Maiddin, Siti Nur Athirah Adibah (2020)
Jal-ja Restaurant is a partnership business that starts its operation in Kota Bharu, Kelantan. Our places will be open 6 days in a week from 12 pm until 10 pm. It is equally owned and managed by its four partners. Jal-ja Restaurant aims to offer its products at a competitive price to meet the demand of the middle to higher income local market area. The company is willing to hire more employees to handle customer service and day to day operations such as waitress, chef, and cashier.